Neo-Exoticism Discourses in Indonesian Online Media: Normalizing Cultural Tourism Regime amid Market Economy - Ikwan Setiawan; Albert Tallapessy; Andang Subaharianto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
This article explores the construction of neo-exoticism discourses in Indonesian online news media. Drawing on online news media research, we show how the transformation of ethnic cultures in Banyuwangi, East Java, Indonesia were positioned as the basis of various tourism events using the representation theory with the discursive constructionist approach. We focus on how some Indonesian online news media reported and positioned Banyuwangi Festival through quotations of government’s official’s statements and descriptions of cultural events that emphasize the transformation of ethnic cultures to meet national and global tourism markets. In doing so, Indonesian online news media actively produced, promoted, and distributed discourses of neo exoticism by emphasizing the beauty of certain of traditional rites, fashions, and arts in various carnivals and festivals. In addition, the media constructed neo-exoticism discourses as a formulas to popularize cultural and touristic events which proved to be beneficial, economically, for local people. However, we argue that broadcasting neo-exotic narratives also created online news media discursive subjects that normalize tourism regimes as managed by the cooperation of government and investors.